1989
DOI: 10.1152/jn.1989.61.3.607
|View full text |Cite
|
Sign up to set email alerts
|

EPSPs in rat neocortical neurons in vitro. I. Electrophysiological evidence for two distinct EPSPs

Abstract: 1. To investigate excitatory postsynaptic potentials (EPSPs), intracellular recordings were performed in layer II/III neurons of the rat medial frontal cortex. The average resting membrane potential of the neurons was more than -75 mV and their average input resistance was greater than 20 M omega. The amplitudes of the action potentials evoked by injection of depolarizing current pulses were greater than 100 mV. The electrophysiological properties of the neurons recorded were similar to those of regular-spikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
68
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 32 publications
21
68
0
2
Order By: Relevance
“…The late EPSPs reported here by afferent stimulation in slices taken from developmentally mature rats (ie 6-8 weeks; Zhu, 2000) resemble the late EPSPs evoked in layer II/III frontal cortical pyramidal neurons by intracortical stimulation in slices from young prepubertal rats (o6 weeks; 120-150 g; Sutor and Hablitz, 1989) or in guinea-pig neocortical neurons that were characterized as stimulus intensity sensitive (Connors et al, 1982), as similarly reported here (see Figure 8). These neurons, which were mostly recovered in cortical deep layer V following intracellular recording/ labeling, had axons which ramified extensively and ascended to superficial layers, in addition to giving off several secondary axons that target subcortical structures (see Figure 1c).…”
Section: Discussionsupporting
confidence: 81%
“…The late EPSPs reported here by afferent stimulation in slices taken from developmentally mature rats (ie 6-8 weeks; Zhu, 2000) resemble the late EPSPs evoked in layer II/III frontal cortical pyramidal neurons by intracortical stimulation in slices from young prepubertal rats (o6 weeks; 120-150 g; Sutor and Hablitz, 1989) or in guinea-pig neocortical neurons that were characterized as stimulus intensity sensitive (Connors et al, 1982), as similarly reported here (see Figure 8). These neurons, which were mostly recovered in cortical deep layer V following intracellular recording/ labeling, had axons which ramified extensively and ascended to superficial layers, in addition to giving off several secondary axons that target subcortical structures (see Figure 1c).…”
Section: Discussionsupporting
confidence: 81%
“…For example, the latency to peak of the late EPSP in vivo (22 ms) was shorter than that obtained under control conditions in vitro (-50 ms), but similar to that of the pharmacologically isolated late EPSP (28 ms). Further, the optimal interpulse interval for eliciting the augmenting response (100-150 ms) was shorter than that optimal for paired-pulse facilitation of the late EPSP in vitro (200-300 ms Sutor & Hablitz, 1989a;) undoubtedly reflect partial suppression by IPSPs. Overlap with the early EPSP underlies the consistent observation that it contains a small but significant NMDA receptor-mediated component (Jones & Baughman, 1988;Hwa & Avoli, 1992).…”
Section: Pharmacological Agentsmentioning
confidence: 96%
“…9Ba; al. 1964;Douglas & Martin, 1991;Ferster & Jagadeesh, 1992;Metherate & Ashe, 1993a, b;Nunez et al 1993) and in vitro (Connors et al 1982;Jones & Baughman, 1988;Sutor & Hablitz, 1989a;Higashi et al 1991;Cox et al 1992). Synaptic interactions studied using the in vitro slice preparation probably occur in vivo, as well.…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…In general, it has been observed that periodicity or temporal envelope coding degrades along the ascending auditory pathway (Joris et al, 2004), presumably due to the intervening synaptic relay (Berry et al, 1976;Miles, 1986;Sutor et al, 1989). If those principles also apply to auditory cortex, temporal resolution should be greater in the core than the belt areas.…”
Section: Introductionmentioning
confidence: 99%